Pengaruh Model Project Based Learning (PjBL) Berbasis STEM Pada Materi Pokok Ekosistem Terhadap Keterampilan Berpikir Kritis Siswa - Citra Partika Dwi; Kartika Manalu (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the effect of the Science, Technology, Engineering, and Mathematics (STEM)-based Project Based Learning (PjBL) model on students’ critical thinking skills in ecosystem learning among tenth-grade students at SMA Al-Ma’shum Kisaran Barat. This study employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The population consisted of 105 tenth-grade students, and the samples were selected through cluster random sampling, resulting in one experimental class and one control class. The research instrument was an essay-based critical thinking test developed according to Facione’s critical thinking indicators, including interpretation, analysis, evaluation, inference, explanation, and self-regulation. Data were analyzed using normality tests, homogeneity tests, and an Independent Sample t-Test with IBM SPSS Statistics for Windows Version 29.0. The results showed that the mean pretest score of the experimental class increased from 31.25 to 86.46 in the posttest, while the control class increased from 30.00 to 75.38. The normality test indicated that the data were normally distributed (Sig. = 0.200 > 0.05), while the homogeneity test showed homogeneous variances (Sig. = 0.328 > 0.05). Furthermore, the Independent Sample t-Test obtained a significance value of 0.000 (< 0.05), indicating a significant effect of the STEM-based PjBL model on students’ critical thinking skills. Therefore, project-based learning integrated with STEM encouraged students to actively engage in problem-solving, scientific investigation, data analysis, and decision-making processes, thereby developing their critical thinking skills more optimally than conventional learning. Keywords: Biology Learning, Critical Thinking Skills, Ecosystem, Project Based Learning, STEM